Review of Maritime Transport 2012 - United Nations Conference on Trade; Development (United Nations, 2012)
More than 80 per cent of international trade in goods is carried by sea and an even higher percentage of developing-country trade is carried in ships. The Review of Maritime Transport, an annual publication prepared by the Division on Technology and Logistics of the UNCTAD secretariat, is an important source of information on a vital sector. It closely monitors developments affecting world seaborne trade, freight rates, ports, surface transport and logistics services, as well as trends in ship ownership control and fleet age, tonnage supply and productivity. The review contains information on legal and regulatory developments and includes an in-depth focus annually on a selected topic.